Effectiveness of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders Among Veterans With Posttraumatic Stress Disorder: A Pilot Study. Issue 2 (March 2018) - Varkovitzky, Ruth L.; Sherrill, Andrew M.; Reger, Greg M.
Effective treatment options are needed for veterans who do not participate in trauma-focused psychotherapy. Research has yet to examine the effectiveness of transdiagnostic psychotherapy in veterans with posttraumatic stress disorder (PTSD) and co-occurring psychological disorders. This pilot study examined the effectiveness of the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders (UP) delivered in a 16-week group format. We examined treatment outcomes in male and female veterans ( n = 52) in an outpatient specialty PTSD clinic at a large Veterans Affairs (VA) medical center. We hypothesized significant decreases in emotion regulation difficulty (Difficulties in Emotion Regulation Scale), PTSD symptom severity (PTSD Checklist for DSM-5 ), and depressive symptom severity (Patient Health Questionnaire–9). In addition, we hypothesized that reductions in emotion regulation difficulty across treatment would negatively predict PTSD and depressive symptoms at posttreatment. PTSD symptoms, depressive symptoms, and emotion regulation difficulty all evidenced significant improvements at the end of treatment relative to baseline ( p s < .001). In addition, reductions in emotion regulation across treatment were associated with lower PTSD and depressive symptoms at posttreatment ( p s < .001). This pilot study provides preliminary evidence supporting use of UP among veterans with PTSD and co-occurring disorders. Well-designed clinical trials evaluating efficacy of UP among veterans are needed.